The Guelph Water connection: The contribution of Actor-Network Theory (ANT) to the study of water management in Guelph, Ontario - GRAVEL, Nathalie; KONÉ, Adama (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l’Université Laval, 2017)
The application of Actor-Network Theory (ANT) to the case of water management in the municipality of Guelph, Ontario, located at the periphery of Toronto, highlights the interactions between the multiple water actors in Canada who, while organised as an informal network, build knowledge together on “blue” and resilient cities. It provides a cross-cutting look at water resource co-management and the process of multiscalar public policy development by considering exchanges and negotiations between administrative bodies, the pan-Canadian water network and the organized local civil society. The water soft path approach has federated the actors of the network who share/build ideas together about sustainable municipal water management. The study of the water nexus in Guelph, of its territoriality and its history, allows for a better understanding of how and why a conservationist culture embracing the principles of “green living” has developed in Guelph and why it has become a centre for water innovation in Canada.